2009
DOI: 10.1590/s0102-09352009000600003
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de probióticos sobre a digestibilidade, escore fecal e características hematológicas em cães

Abstract: RESUMOAvaliaram-se os efeitos da suplementação de dois tipos de probióticos para cães filhotes, que receberam dois tipos de dieta -de alta e de baixa qualidade -, sobre a digestibilidade dos nutrientes, escore fecal e parâmetros sanguíneos. Foram utilizados 18 animais, distribuídos em três tratamentos. No tratamento 1, controle, os cães receberam somente a ração; no tratamento 2, ração com probiótico 1 (Bifidobacterium) e, no tratamento 3, ração com probiótico 2 (Lactobacillus). O experimento foi dividido em d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
2
3
0
2
Order By: Relevance
“…Likewise, no changes were observed in dogs' faecal pH, in agreement with what has been reported by Swanson et al [1], Félix et al [6], and Stercova et al [19]. On the other hand, Feliciano et al [5] observed a reduction in faecal pH of dogs fed a diet containing Lactobacillus spp. The absence of faecal pH alterations of dogs fed with Bacillus spp.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Likewise, no changes were observed in dogs' faecal pH, in agreement with what has been reported by Swanson et al [1], Félix et al [6], and Stercova et al [19]. On the other hand, Feliciano et al [5] observed a reduction in faecal pH of dogs fed a diet containing Lactobacillus spp. The absence of faecal pH alterations of dogs fed with Bacillus spp.…”
Section: Discussionsupporting
confidence: 87%
“…DFM has been defined by the US Food and Drug Administration as the feed product containing the source of naturally-existing live microbes, like some bacteria of the Bacillus genus. When supplemented in the diet, these microorganisms may favour non-pathogenic bacteria [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Saad et al (2011) (Biourge et al, 1998). Estudos realizados por Feliciano et al (2009) demonstraram que a adição de probióticos na alimentação de cães não alterou a digestibilidade do alimento. O escore fecal foi alterado positivamente somente quando a alimentação dos cães foi substituída de Standard para Super Premium.…”
Section: Probióticosunclassified
“…The DFM has been defined by the US Food and Drug Administration as the feed product containing the source of live naturally existing microbes, as some bacteria of genus Bacillus. When supplemented in the diet, these microorganisms may favor non-pathogenic bacteria [5,6].…”
Section: Introductionmentioning
confidence: 99%